The The Relationship Between Parental Income and the Role of Parental or Babysitter Care on the Incidence of Stunting - Rahma Fadila, Zakiya Nur; Sulistiawati, Sulistiawati; Setyoboedi, Bagus (Rifa'Institute, 2025)
Introduction: Nutrition plays a crucial role in child growth and development. In Indonesia, stunting remains a major public health problem, with a prevalence of 21.5%, influenced by maternal health, socioeconomic conditions, and caregiving practices. Objective: This study aimed to determine the relationship between parental income, parental caregiving, and babysitter caregiving with stunting among children aged 24–59 months in the working area of the Ponggok Community Health Center in 2025. Method: This study employed an observational analytic method with a retrospective case–control design and was not a case report. The population consisted of mothers with toddlers aged 24–59 months. A total of 84 respondents were selected using consecutive sampling, comprising 42 stunted toddlers (case group) and 42 non-stunted toddlers (control group). Stunting status was determined based on height-for-age z-scores (HAZ) according to WHO standards. The independent variables were family income and caregiving roles of parents and babysitters, while the dependent variable was stunting incidence. Data were collected from Maternal and Child Health (KIA) books and structured questionnaires and analyzed using univariate analysis and Chi-Square tests (p < 0.05). Result and Discussion: Parental income was not significantly associated with stunting (p > 0.05), suggesting that income alone may not directly determine child growth outcomes. Factors such as nutrition knowledge, resource allocation, access to health services, and environmental conditions may influence this relationship. Conclusion: In contrast, parental and babysitter caregiving roles showed significant associations with stunting (p < 0.05), highlighting the importance of caregiving quality.